Learning and collaboration technologies : novel learning ecosystems : 4th International Conference, LCT 2017, held as part of HCI International 2017, Vancouver, BC, Canada, July 9-14, 2017, proceedings - (:unkn) unknown (My University, 2017)
The two-volume set LNCS 10295 and 10296 constitute the refereed proceedings of the 4th International Conference on Learning and Collaboration Technologies, LCT 2017, held as part of the 19th International Conference on Human-Computer Interaction, HCII 2017, in Vancouver, BC, Canada, in July 2017, in conjunction with 15 thematically similar conferences. The 1228 papers presented at the HCII 2017 conferences were carefully reviewed and selected from 4340 submissions. The papers cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The papers included in this volume are organized in the following topical sections: multimodal and natural interaction for learning; learning and teaching ecosystems; e-learning, social media and MOOCs; beyond the classroom; and games and gamification for learning.
Keywords: Augmented reality; Big data; Communication networks; Online learning; Social networks; Adaptive learning; Bioinformatics; Blended learning; Child-computer interaction; Collaborative learning; Cooperative learning; Distributed security; E-learning; Game-based learning; Human-computer interaction; Mixed reality; Mobile learning; Security; Social Web; Virtual reality